REVISITING SOCIAL DETERMINANTS OF HEALTH: A POLITICAL ECONOMY PERSPECTIVE - Clarke, Benjamin Thomas; Harrison, Sophia Grace (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
Health, as defined by the World Health Organization in 1946, is not merely the absence of disease but a state of complete physical, mental, and social well-being. Achieving this state of well-being, however, remains a challenge with significant disparities across the global population. For the past three decades, these health inequalities have been understood through the lens of the "social determinants of health" (SDH) framework, defined by the WHO as the conditions in which people are born, grow, live, work, and age, along with the fundamental drivers of these conditions. These conditions encompass a wide range of factors, from GDP per capita and educational opportunities to the availability of public transportation and the prevalence of fast-food chains. While the quality of medical care certainly influences health outcomes, the SDH framework emphasizes that it plays a more limited role in determining who becomes ill in the first place. The SDH framework gained significant attention in 2008 with the WHO’s Social Determinants of Health Report. However, despite this attention and awareness, the health gap between social classes in most countries has not significantly narrowed, and in some high-income countries, it has either widened or remained stagnant. A review of the framework in 2020 concluded that it needs revision to address the evolving challenges faced by public health in the coming years, especially in light of the ongoing COVID-19 pandemic.